DISIPLIN KERJA PADA UMKM BATIK SEMARANG 16 - Noah Gabriel Teurah; Ari Pradhanawati (Universitas Diponegoro, 2018)
The informal business sectors or small medium enterprises will surely depend on good and quality human resources to drive their business assets. This is because human resources are a basic element of every company. So every company, especially small medium enterprises will always try to improve employee productivity. One of the factors that can increase productivity drastically is work discipline. This research was conducted at UMKM Batik Semarang 16 producing batik in Semarang city, aiming to know the application of work discipline. The data were collected by participant observation technique, in-depth interview to business leader, and business worker in UMKM Batik Semarang 16. Data analysis was done gradually by describing the condition (description), interpreting with theory (interpretation) and explaining (explanation) from data source obtained. The results of the analysis are compared with supporting theories, among them Malayu Hasibuan (2000: 192) states that there are several factors that affect the level of discipline of employees of a company, such as penalties or written rules, role model of leadership, firmness of leadership, remuneration ,and supervision inherent / monitoring . This study concludes that the discipline of work in UMKM Batik Semarang 16 has been running well, especially in the role model of leadership, firmness of leadership, and supervision inherent / monitoring. But in terms of dimensions of punishment sanction and remuneration must be improved. Suggestions that can be given are 1) Required mechanism of interpretation and socialization of routine about work discipline 2) The need to hold and apply compensation or remuneration and promotion of position to improve discipline worker of workers consistent in discipline. In addition, it is necessary to increase the training or deepening of batik science to the workers.